ANALISIS PREFERNSI KONSUMEN PADA ATRIBUT BUAH PISANG KEPOK DI PASAR TRADISIONAL KOTA SURABAYA - Firmansyah, Ferry; Nugroho, Sigit Dwi; Indah, Pawana Nur (Agridevina : Berkala Ilmiah Agribisnis, 2021)
Understanding consumer preferences is important in the contect of decision making of key stakeholders, including producers themselves, as well as development agencies that operate in the fruit subsector. This research aims to analyse the attributes of yellow kepok banana that became analyse the attributes most considered by the consumers on the decisions to buy yellow kepok banana at traditional market in Surabaya City. The method of this research is case study. Data were collected by interview the respondents directly at tradisional market with the questionnaires. Descrptive analytic method was applied by implementing purposive sampling to get 100 consumets as respondents in this research. The attributes observed are the color of fruit, taste of fruit, size and flavour of fruit. Respondent characteristics and consumer behaviour are analysed by descriptive. Whereas yellow kepok banana preferences were analysed by using chi square. While most considered attributes shown by the calculation of chi square. Yellow kepok banana attributes that consumers the purchase consider include : bright yellow kepok banana fruit color, the taste of yellow kepok banana is a bit sweet, medium size yellow kepok banana (10-14 cm) and sweet yellow kepok banana flavour. DOI : https://doi.org/10.33005/adv.v10i2.2914